Administrative Factors Emphasizing Teachers, School Ecology, and Ethics and Their Influence on the Capacity for Implementing the Student Care and Support System Among Educational Personnel in ROI Et Province: Administrative Factors Emphasizing Teachers, School Ecology, and Ethics and Their Influence on the Capacity for Implementing the Student Care and Support System Among Educational Personnel in ROI Et Province - Kumhom, Naitawan; Moonlasart, Tippawan; Youtakew, Natthaphumin (RATANABUTH JOURNAL, 2026)
The purpose of this research was to investigate the administrative factors emphasizing teachers, school ecology, and ethics, and their relationship with the operational potential of the Student Care and Support System among educational personnel in Roi Et Province. The sample consisted of 385 educational personnel in Roi Et Province, selected using Cochran’s sample size determination table. The research instrument was a questionnaire. The statistics used for data analysis were mean, standard deviation, Pearson’s product-moment correlation coefficient, and stepwise multiple regression analysis. The findings revealed that the administrative factors, namely teachers, school ecology, and ethics, were positively correlated with the operational potential of the Student Care and Support System among educational personnel in Roi Et Province at the .01 level of statistical significance. The overall administrative factors had a high positive correlation with the operational potential (r = .808). The factor with the highest correlation was ethics, particularly achievement motivation (r = .766) and internal locus of control (r = .731), followed by role modeling (r = .624), knowledge (r = .605), technological competency (r = .604), and organizational culture (r = .567), respectively. The results of the stepwise multiple regression analysis indicated that six administrative factors, namely achievement motivation, internal locus of control, role modeling, knowledge, technological competency, and organizational culture, significantly predicted the operational potential of the Student Care and Support System at the .01 level of statistical significance. The multiple correlation coefficient was R = .849, the coefficient of determination was R² = .721, and the adjusted coefficient of determination was Adjusted R² = .718. These six factors jointly explained 72.10% of the variance in the operational potential. Achievement motivation was the strongest predictor (β = .398), followed by internal locus of control (β = .264), role modeling (β = .192), knowledge (β = .176), technological competency (β = .141), and organizational culture (β = .118), respectively.